Indole: An evolutionarily conserved influencer of behavior across kingdoms. (23rd December 2016) - Tomberlin, Jeffery K.; Crippen, Tawni L.; Wu, Guoyao; Griffin, Ashleigh S.; Wood, Thomas K.; Kilner, Rebecca M.
Abstract : Indole is a key environmental cue that is used by many organisms. Based on its biochemistry, we suggest indole is used so universally, and by such different organisms, because it derives from the metabolism of tryptophan, a resource essential for many species yet rare in nature. These properties make it a valuable, environmental cue for resources almost universally important for promoting fitness. We then describe how indole is used to coordinate actions within organisms, to influence the behavior of conspecifics and can even be used to change the behavior of species that belong to other kingdoms. Drawing on the evolutionary framework that has been developed for understanding animal communication, we show how this is diversely achieved by indole acting as a cue, a manipulative signal, and an honest signal, as well as how indole can be used synergistically to amplify information conveyed by other molecules. Clarifying these distinct functions of indole identifies patterns that transcend different kingdoms of organisms. Abstract : Indole and its derivatives play crucial roles as signals and/or cues regulating inter‐kingdom interactions. Deciphering and distinguishing these roles are crucial for understanding the evolutionary underpinnings of trophic level interactions and nutrient recycling within food webs.